The Sappanwood Extract Drying With Carrier Agent Under Air Dehumidification - Djaeni, Mohamad; Triyastuti, Meilya Suzan; Utari, Febiani; Annisa, Arianti Nuur; Novita, Dewi Ayu (IPTEK The Journal for Technology and Science, 2015)
The sappanwood extract enriched by brazilin can be used for natural colouring agent in food and beverages. The extract is produced in form of dry powder for consummer convenience as well as prolonging storage life. Currently, the sappanwood extract drying still deals with the product sticky that inhibit water transport in drying. As a result, the drying process needs long time to get moisture content below 10%. The extract drying with carrier agent is an option to break the product sticky and to enlarge the surface area for water transport.This paper discusses the effect of carrier agent arabic gum and maltodextrin on sappanwood extract drying with air dehumidification. As a responses, the moisture content in extract was observed every sampling time and average drying rate was estimated. Results showed that, the carrier agent improve drying rate significantly. With arabic gum 10%, the average drying time can be 2 hours shorter than that of without carrier agent. With faster drying rate, the drying time was shorter at higher operational temperature. Keywords: Brazilin, dehumidification, tray dryer, zeolite